Development and commissioning of a full‐size prototype fixed‐beam radiotherapy system with horizontal patient rotation. Issue 3 (14th February 2019) - Liu, Paul Zhi Yuan; O'Brien, Ricky; Heng, Soo‐Min; Newall, Matthew; Downes, Simon; Shieh, Chun‐Chen; Corde, Stephanie; Jackson, Michael; Keall, Paul
Abstract : Purpose: Compared to conventional linacs with rotating gantries, a fixed‐beam radiotherapy system could be smaller, more robust and more cost‐effective. In this work, we developed and commissioned a prototype x‐ray radiotherapy system utilizing a fixed vertical radiation beam and horizontal patient rotation. Methods: The prototype system consists of an Elekta Synergy linac with gantry fixed at 0° and a custom‐built patient rotation system (PRS). The PRS was designed to immobilize patients and safely rotate them about the horizontal axis. The interlocks and emergency stops of the linac and PRS were connected. Custom software was developed to monitor the system status, control the motion of the PRS and modify treatment plans for the fixed‐beam configuration. Following installation, the prototype system was commissioned for three‐dimensional (3D) conformal therapy based on guidelines specified in AAPM TG‐45 and TG‐142, with modifications for the fixed‐beam geometry made where necessary. Results: The system and control software was tested in a variety of machine states and executed motion, stop and beam gating commands as expected. Interlocks and emergency stops of the linac and PRS were found to correctly stop PRS motion and both kV and MV radiation beams when triggered. For 3D conformal treatments, the prototype system met all AAPM TG‐45 and TG‐142 specifications for geometric and dosimetric accuracy. Motion of the PRS was within 0.6 ± 0.3 mm and 0.10° ± 0.07° of input values for translation and rotation respectively. The axis of rotation of the PRS was coincident with the radiation beam axis to less than 1 mm. End‐to‐end treatment verification for 6 MV conformal treatments showed less than 2% difference between planned and delivered dose for all fields. Conclusion: In this work, we have developed and commissioned a radiotherapy system that utilizes a fixed vertical radiation beam and horizontal patient rotation. This system is a proof‐of‐concept prototype for a fixed‐beam treatment system without a rotating gantry. Fixed‐beam systems that are smaller and more cost‐effective could help in improving global access to radiotherapy.